DESCARTES’ ONTOLOGY AND THE IDEA OF NATURE CONTROL - Česlovas Kalenda (Problemos)
The idea of nature control in Western civilisation is not only connected with ecological-climatic conditions as well as with social conditions but also with the nature of people and the properties of thinking, which are only typical to the human brain’s functional asymmetry. It was decisive in the West, differently from the East, that a rational, analytic rudiment was developed which legalized the antipode between subject and object, nature and spirit. Being one of the most outstanding successors of this tradition R. Descartes, a pupil of the Jesuit college, was devoted to a comparatively moderate position concerning the problems of nature control without any claim to global domination that was distinct to the gnosticism and hermetism of that time. Descartes’ ontology based on rationalism has, however, contributed to the strengthening of the mechanistic world model and, owing to it, granted a philosophical approval of man’s aspiration to remake and control nature.